Studi Potensi Pemanfaatan Biomassa Nipah (Nypa fruticans) sebagai Bahan Baku Kukis dan Kelayakan Usahanya di Desa Simpang Tiga Abadi, Kabupaten Ogan Komering Ilir - Rosianty, Yuli; Harbi, Jun; Riani, Fitri; Harefa, Ribka (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The study aims to determine the potential of nipa palms in Simpang Tiga Abadi Village, to analyze the financial feasibility of the nipa cookie business, and to assess the non-financial aspects of the nipa flour cookie business in the same area. This study employs both qualitative and quantitative approaches. The qualitative approach examines non-financial aspects such as legal, socioeconomic, market, and management factors through interviews, while the quantitative approach analyzes the potential of nipa palms and the financial aspects of the nipa flour cookie business through calculations of clump density, flour yield, income, Revenue Cost Ratio (R/C), and Break Even Point (BEP). The results show that one hectare of nipa stands produces approximately 3.98 tons of nipa flour, indicating that the natural availability of nipa flour is sufficient for the Kelompok Tani Usaha Bintang Ratu (Bintang Ratu Farmers Group). The financial feasibility analysis indicates that the nipa flour cookie business managed by the group is profitable and viable. The non-financial aspects—including legal, socioeconomic, management, and human resources—are also favorable, suggesting that the business has good potential for future development, except for the market and marketing aspects, which remain a limitation for the group in promoting their products to stores.